Language Technology for Cultural Heritage 2011
DOI: 10.1007/978-3-642-20227-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Wiki Systems, Natural Language Processing, and Semantic Technologies for Cultural Heritage Data Management

Abstract: Modern documents can easily be structured and augmented to have the characteristics of a semantic knowledge base. Many older documents may also hold a trove of knowledge that would deserve to be organized as such a knowledge base. In this chapter, we show that modern semantic technologies offer the means to make these heritage documents accessible by transforming them into a semantic knowledge base. Using techniques from natural language processing and Semantic Computing, we automatically populate an ontology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In contrast to Wikulu and our previous work in the Durm project [9], in this paper we offer a general architecture that allows any wiki to benefit from various NLP techniques brokered via the Semantic Assistants framework. In other words, our Wiki-NLP integration is not only NLP service independent, but also offers a flexible and easily extensible design for the integration of various wiki engines with NLP capabilities.…”
Section: Related Workmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast to Wikulu and our previous work in the Durm project [9], in this paper we offer a general architecture that allows any wiki to benefit from various NLP techniques brokered via the Semantic Assistants framework. In other words, our Wiki-NLP integration is not only NLP service independent, but also offers a flexible and easily extensible design for the integration of various wiki engines with NLP capabilities.…”
Section: Related Workmentioning
confidence: 93%
“…To preserve these artifacts, they are often digitized and stored in nationally and internationally distributed databases. We previously developed a custom wiki integration for this scenario, the Durm Wiki, 17 where we demonstrated how modern semantic technologies offer the means to make these heritage documents accessible by transforming them into a semantic knowledge base [9]. Now we are able to offer the same NLP capabilities that had been implemented in the Durm wiki using our generic Wiki-NLP integration architecture, in addition to all the other services made available through the general Semantic Assistants framework.…”
Section: Cultural Heritage Data Managementmentioning
confidence: 95%
See 2 more Smart Citations
“…The generated index page, as shown in Figure 4, presents an alphabetically-ordered list of wiki terms and a direct link to their pages inside the wiki. In experiments with end users, we found that the presence of such an automatically maintained index page not only aggregates the wiki's embodied content on a high-level and enables users to find information at a glance, but also helps them to "discover" interesting concepts or entities that they did not know were present in the wiki [6]. platform, have demonstrated their capabilities in requirements engineering processes.…”
Section: Scenario 2: Cultural Heritage Data Managementmentioning
confidence: 99%